Export of Seeds-History, Present Status and Future Prospects - Thakur, Ashok K.; Sarkar, N. C.; Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
The movement of seeds of cultivated plants started with the movement of man across nations and continents. However, the formal trade of seeds was started with the establishment of the Fédération Internationale du Commerce des Semences (FIS) (International Seed Trade Federation) in The First International Seed Congress held in London in 1924. In 1938, the International Association of Plant Breeders for the Protection of Plant Varieties (ASSINSEL, the acronym derived from French for Association Internationale des Sélectionneurs pour la Protection de Obentions Végétales) was established with the chief objective to adopt international norms for protection of plant varieties. With the aim of encouraging the development of new varieties of plants, the International Union for the Protection of New Varieties of Plants (UPOV) was established in 1961 by the International Convention for the Protection of New Varieties of Plants (the “UPOV Convention”)